The Adoption of Sustainable Facilities Management Practices in Organisations: A study of Malaysian universities - Hasim, Mohamad Sufian; Abdullah, Ahmad Sharim; Abdul Rasam, Abdul Rauf; Ismail, Hafiszah (Environment-Behaviour Proceedings Journal, 2020)
Globally, there is a growing trend among organisations towards promoting sustainability as an essential business strategy due to a high level of awareness about the impacts of their operations on the triple bottom line. This paper aims to examine the implementation of sustainability practices in an organisation focusing on universities. The objective was to determine sustainability adopted in facilities management (FM) practice concerning three different sustainability dimensions. Sixteen (16) interviews were conducted with the senior managerial level in selected universities. Among all dimensions, environmental sustainability was widely focused on having higher priorities for energy efficiency, waste reduction, and water conservation. These results provided some explanation and understanding of the overall picture of the study about organisational commitment towards sustainability in facilities management. Keywords: Sustainable Facilities Management; Malaysian Universities; Sustainable Organisation; Facilities Management eISSN: 2398-4287 Â© 2020. The Authors. Published for AMER ABRA cE-Bs by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peerâ€“review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia. DOI: https://doi.org/10.21834/e-bpj.v5i13.1898